Design games as fieldwork: Re-visiting design games from a design anthropological perspective. (March 2021) - Kjaersgaard, Mette Gislev; Knutz, Eva; Markussen, Thomas
Abstract : This article explores how design games might serve as a form of design anthropological fieldwork drawing on examples from the project 'Changing Perspectives'- a social design project aimed at designing games to support family consultants in working with incarcerated fathers' empathic understanding of how their children and family experience the collateral effects of imprisonment. In this design anthropological approach to design games, focus shifts from how games facilitate collaboration to how they can help design researchers understand the ambiguous roles of the design researcher vis-à-vis participants, the gap between research intentions and situated practices, and stakeholder agonism to help us discover and challenge implicit assumptions and roles embedded in the design project. Highlights: Designing games can support family consultants' work with incarcerated fathers. Design games can serve as a form of design anthropological fieldwork. During fieldwork design games help challenge assumptions in the design project.